Introduction of sorghum [Sorghum bicolor (L.) Moench] green manure in rotations of head salads and baby leaf crops under greenhouse - Morra, Luigi; Cerrato, Domenico; Bilotto, Maurizio; Baiano, Salvatore (Italian Journal of Agronomy, 2017)
This paper deals with the introduction in tunnel-greenhouses of sweet sorghum cultivated in short, summer cycle as green manure with the aim to amend soils with biomass grown on farm. This practice has been spreading in tunnels of Sele river Valley (Salerno, Italy) where baby leaf crops are cultivated in numerous cycles (up to 5-7) per year. Three sorghum varieties for forage or biomass (Goliath, BMR 201, and BMR 333) were cultivated in two farms at Eboli and San Marzano sul Sarno with the aim of studying their responses in term of fresh and dry aboveground biomass yielded, carbon (C) and nitrogen (N) content of the biomass incorporated in soil, and C balance in amended soils after one year of ordinary cash crop sequences. No differences, with regard to all the parameters measured, were pointed out among the tested varieties in each site. The sorghum cycle lasted 45 days at Eboli, yielding on average 98 and 13 t ha–1 of fresh and dry biomass, respectively; soil biomass incorporation supplied on average 5.8 t ha–1 of organic C and 273 kg ha–1 of total N. In the farm of San Marzano, sorghum cycle lasted 68 days, yielding 116 and 18 t ha–1 of fresh and dry biomass, respectively; soil biomass incorporation supplied on average 8 t ha–1 of organic C and 372 kg ha–1 of total N. After one year, the plots amended with sorghum biomass showed a soil organic carbon (SOC) concentration not different from the starting point, while SOC decreased in fallow plots. At Eboli, initial SOC content was 12.3 g kg–1, but one year later it resulted 12.3, 12.8, 12.2 and 11.3 g kg–1 in BMR 201, BMR 333, Goliath and control plots, respectively. At San Marzano, initial SOC content was 11.4 g kg–1, but one year later it resulted 11, 12, 10.7 and 10.5 g kg–1 in BMR 201, BMR 333, Goliath and control plots, respectively. The annual C balance put in evidence that the green manure with sorghum biomass caused SOC losses higher than those detected in fallow plots. This let us suppose a prime effect in boosting the soil microbial C mineralisation. Only cv BMR 333 in the Eboli trial pointed out a positive SOC change of 1.8 t ha–1. Further studies are requested to better understand the real efficacy of sorghum cover crop in soil amendment under tunnels devoted to intensive vegetable crop sequence.